2017
DOI: 10.1158/1535-7163.mct-17-0075
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of EGFR Wild-Type Non–Small Cell Lung Cancer Cells to EGFR-Tyrosine Kinase Inhibitor Erlotinib

Abstract: The benefit of EGFR-TKI in non-small cell lung cancer has been demonstrated in mutant EGFR tumors as first-line treatment but the benefit in wild-type EGFR tumors is marginal as well as restricted to maintenance therapy in pretreated patients. This work aimed at questioning the effects of cisplatin initial treatment on the EGFR pathway in non-small cell lung cancer and the functional consequences and in animal models of patient-derived xenografts (PDX). We establish here that cisplatin pretreatment specificall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Platinum-based chemotherapy and the first-generation TKIs have been used as the first-line treatment for NSCLC patients carrying wild-type and mutant EGFRs, respectively [15,16,23,24]. However, acquired drug resistance is inevitable after a progression-free period of approximately 9 to 13 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platinum-based chemotherapy and the first-generation TKIs have been used as the first-line treatment for NSCLC patients carrying wild-type and mutant EGFRs, respectively [15,16,23,24]. However, acquired drug resistance is inevitable after a progression-free period of approximately 9 to 13 months.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin (CDDP), a platinum-based chemotherapeutic drug, has been commonly used to treat a wide range of solid malignancies, including lung cancer [10,11]. CDDP is the standard regimen in the first-line chemotherapy for patients with advanced stage NSCLC [10,12,13,14], especially patients carrying wild-type EGFR [15,16]. After cellular uptake, CDDP becomes a positively charged aquo complex that can interact with deoxyribonucleic acid (DNA) to form intra- and inter-strand cross-links, resulting in apoptosis induction [10,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, some patients with lung cancer with wild-type EGFR benefit from EGFR-TKI therapy, 9,10 possibly because resistance to EGFR-TKIs can be mediated through multiple signalling pathways that converge upon cap-dependent translation in NSCLC cells expressing wild-type EGFR. 11,12 Interestingly, our previous study showed that CD73 affected the efficacy of EGFR-targeted therapies in NSCLC cells with wild-type EGFR. 13 Thus, based on the literature, we hypothesized that NRP1 plays a role in the EGF signalling pathway and that knockdown of NRP1 expression might sensitize NSCLC cells to therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we aimed to assess the response to EGFR-TKIs of cancer cells with EGFR/KRAS co-mutations. Using CRISPR/Cas9 genome editing, we successfully generated isogenic cell lines with one or two copies of L858R EGFR mutation, one of the most common types of EGFR mutation [4], from A549 cells, a well-established cell line harboring homozygous G12S KRAS mutation but wild-type EGFR [20][21][22]. Comparison of TKI sensitivity among these cell lines showed that EGFR/KRAS co-mutated cells were more sensitive than parent cells, indicating that EGFR-TKIs may represent a treatment option for cancers harboring EGFR/KRAS co-mutation.…”
Section: Introductionmentioning
confidence: 99%